Cultural Identity Through Symbolism: The Role of Provincial Seals in Thai City Branding and Regional Development - Chawaroj Chawanawech; Prapatpong Upala (Journal of Community Development Research (Humanities and Social Sciences), 2025)
This research examines Thailand’s provincial seals as symbolic tools of local identity construction and civic representation within the broader framework of city branding and regional development. The objective of this research is to investigate how these official symbols contribute to the construction of brand identity within the Thai urban context. While existing literature on city branding largely focuses on contemporary visual strategies in Western contexts, this study highlights the role of historically rooted symbols specifically, provincial seals as visual expressions of place identity in Thailand. Originally introduced during a period of state-led modernization in the mid-20th century, these seals remain in active use and are deeply embedded in local cultural narratives. This study employed a qualitative research design. Data were collected using a structured observation form from all 76 provinces of Thailand and one special administrative region (Bangkok). The collected data were analyzed through content analysis focusing on visual components to identify and interpret the characteristics and symbolic meanings within the observed materials. The result categorizes symbolic elements into two primary identity types: tangible (e.g., architecture, landscapes, animals, agriculture) and intangible (e.g., myths, beliefs, local names, handicrafts). Findings reveal that most seals contain hybrid identity structures, combining two to three symbolic elements that reflect a region’s physical characteristics and intangible cultural heritage. The most frequently represented categories include historical and mythological themes, followed by religious architecture and geographic landmarks. Regional analysis shows diverse patterns of symbolic emphasis, corresponding to local traditions and socio-cultural environments. These visual narratives reinforce collective memory, local pride, and cultural continuity. The study argues that provincial seals function as more than administrative insignias; they serve as cultural artifacts that contribute to community identity, visual storytelling, and decentralized development. This research contributes to the field of community development by demonstrating how traditional symbols can inform contemporary city branding strategies rooted in cultural authenticity and local engagement.
Keywords: Southeast Asian Sociopolitical Studies; Cultural Heritage Management and Preservation; Diverse Aspects of Tourism Research